Football (as) Guanxi: a relational analysis of actor reciprocity, state capitalism, and the Chinese football industry. Issue 12 (1st December 2020) - Xue, Hanhan; Watanabe, Nicholas M.; Chen, Ryan; Newman, Joshua I.; Yan, Grace
Abstract: Recently, private and State actors within the Chinese economy have increasingly taken ownership of (or established other financial relationships with) major football clubs across Asia and Europe. In this study, we provide an abductive interpretation of a) the extent to which capital investitures in the sport are linked to State mandates to grow influence in the game in China and abroad and b) how, by investing in these clubs, business actors are able to strategically ensconce themselves in political capital-yielding social networks. We use the concept of guanxi —or relationship building through gifting and reciprocity—to theorize the machinations through which these networks are formed. We then utilize social network analysis to map how, amidst shifting State mandates, private actors have mobilized football-based capital as a form of gifting to (re)assemble football-based networks that strategically position their firms in configurations that might maximize political capital.